Inhibitory effects of aptamer targeted teicoplanin encapsulated PLGA nanoparticles for Staphylococcus aureus strains - Ucak, Samet; Sudagidan, Mert; Borsa, Baris A.; Mansuroglu, Banu; Ozalp, Veli C. (SPRINGER, 2020)
Emergence of resistance to traditional antibiotic treatments necessitates alternative delivery systems. Teicoplanin is a glycopeptide antibiotic used in the treatments of serious infections caused by Gram-positive bacteria, including Methicillin Resistant Staphylococcus aureus (MRSA). One strategy to keep up with antibiotic resistance development is to limit dose and amount during treatments. Targeted delivery systems of antibiotics have been suggested as a mechanism to slow-down the evolution of resistance and to increase efficiency of the antimicrobials on already resistant pathogens. In this study, we report teicoplanin delivery nanoparticles of Poly Lactic-co-Glycolic Acid (PLGA), which are functionalized with S. aureus specific aptamers. A 32-fold decrease in minimum inhibitory concentration (MIC) values of teicoplanin for S. aureus was demonstrated for susceptible strains and about 64-fold decline in MIC value was achieved for moderately resistant clinical isolates of MRSA upon teicoplanin treatment with aptamer-PLGA nanoparticles. Although teicoplanin delivery in PLGA nanoparticles without targeting demonstrated eightfold decrease in MIC of susceptible strains of S. aureus and S. epidermidis and twofold in MIC of resistant strains, the aptamer targeting specifically decreased MIC for S. aureus, but not for S. epidermidis. Therefore, aptamer-targeted PLGA delivery of antibiotic can be an attractive alternative to combat with some of the multi-drug resistant bacterial pathogens.
Keywords: Antibiotics; MRSA; Nanoparticles; Aptamers; Staphylococcus aureus; MOLECULAR TOOLS; VANCOMYCIN; DELIVERY; Biotechnology & Applied Microbiology